2012
DOI: 10.5402/2012/613595
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation in Primary Motor and Somatosensory Cortices during Motor Imagery Correlates with Motor Imagery Ability in Stroke Patients

Abstract: Aims. While studies on healthy subjects have shown a partial overlap between the motor execution and motor imagery neural circuits, few have investigated brain activity during motor imagery in stroke patients with hemiparesis. This work is aimed at examining similarities between motor imagery and execution in a group of stroke patients. Materials and Methods. Eleven patients were asked to perform a visuomotor tracking task by either physically or mentally tracking a sine wave force target using their thumb and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 70 publications
4
31
2
1
Order By: Relevance
“…It is not known whether being able to perform MI tasks is necessary to gain benefit from it in clinical practice (8,9). Moreover, Confalonieri et al report that motor imagery stimulates sensorimotor and pre-motor areas even in poor imagers with stroke (25). In our study we found no correlation between motor imagery ability (as reflected by initial MIQ-RS scores) and our outcome measure of gait velocity improvement after motor imagery training.…”
Section: Effect Of Motor Imagery Training On Motor Imagery Abilitycontrasting
confidence: 51%
“…It is not known whether being able to perform MI tasks is necessary to gain benefit from it in clinical practice (8,9). Moreover, Confalonieri et al report that motor imagery stimulates sensorimotor and pre-motor areas even in poor imagers with stroke (25). In our study we found no correlation between motor imagery ability (as reflected by initial MIQ-RS scores) and our outcome measure of gait velocity improvement after motor imagery training.…”
Section: Effect Of Motor Imagery Training On Motor Imagery Abilitycontrasting
confidence: 51%
“…Previous studies (Page et al, 2001 ; Butler and Page, 2006 ; Confalonieri et al, 2012 ) have shown that the combination of MP and PT is helpful in improving functional and motor skills more than MP only. MP by itself is considered an effective technique to enhance motor performance by tracing the overlap between motor imagery and motor execution neural circuits (Jeannerod, 2006 ).…”
Section: Discussionmentioning
confidence: 96%
“…The first two images of every EPI-recording session were discarded to account for the approach to steady state in the MR signal. Prior to image analysis, each participant's raw data of fMRI scan were motion-corrected and normalized, similar to the previous study [37]. The amount of absolute motion did not exceed 1 mm for any participant.…”
Section: Methodsmentioning
confidence: 99%